Expert System for Skin Disease Diagnosis Using the Best First Search Method and Fuzzy Tsukamoto - Fahry, Fahry; Adam, M. Awaludin; Hidjah, Khasnur; Azwar, Muhammad; Hairani, Hairani (Journal of Electrical Engineering and Computer (JEECOM), 2025)
The skin is the largest organ and is vulnerable to various diseases, which can spread through direct contact or the environment. Skin diseases are among the ten most common conditions in outpatient care in Indonesia, often caused by poor hygiene and environmental exposure. The limited number of dermatologists makes diagnosing and treating skin diseases more challenging. This study develops an expert system for diagnosing skin diseases using the Best First Search method and Fuzzy Tsukamoto, serving as an alternative or complement to medical diagnosis. Best First Search prioritizes diagnoses based on predefined rules, while Fuzzy Tsukamoto adds flexibility in assessing disease severity. Testing shows that the system achieves an accuracy of 83.3%, demonstrating its potential to assist patients and medical professionals in improving diagnostic efficiency and healthcare quality for skin diseases.